2022
DOI: 10.1097/jd9.0000000000000245
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotection Knowledge and Photoprotective Behavior of University Students: A Cross-sectional Study in Indonesia

Abstract: Objective: Awareness regarding the negative effects of ultraviolet radiation are commonly neglected in Asian countries. This study sought to evaluate the ultraviolet radiation knowledge and photoprotective behaviors of university students in Indonesia. Methods: This observational cross-sectional was conducted at Pelita Harapan University, Indonesia. Results: A total of 89 (45.4%) medical students and 107 (54.6%) nonmedical students participated in this study. Their mean age was 21.03 ± 2.03 years, and 46.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…18 A cross-sectional study of 196 university students in Indonesia reported that 46% of participants had FST III and around 80-90% were aware of the most important risks of sun exposure (hyperpigmentation, skin cancer, photoaging, and photodermatoses). 19 However, almost two-thirds were not familiar with UV radiation wavelengths (UVA, UVB, and UVC) or that PA indicates protection against UVA. 19 In conclusion, our epidemiological data demonstrated that the survey respondents in three Asian countries (China, Indonesia, and Japan) may underestimate the risk of sun exposure and education is needed on the risks and benefits of photoprotection, especially for children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 A cross-sectional study of 196 university students in Indonesia reported that 46% of participants had FST III and around 80-90% were aware of the most important risks of sun exposure (hyperpigmentation, skin cancer, photoaging, and photodermatoses). 19 However, almost two-thirds were not familiar with UV radiation wavelengths (UVA, UVB, and UVC) or that PA indicates protection against UVA. 19 In conclusion, our epidemiological data demonstrated that the survey respondents in three Asian countries (China, Indonesia, and Japan) may underestimate the risk of sun exposure and education is needed on the risks and benefits of photoprotection, especially for children.…”
Section: Discussionmentioning
confidence: 99%
“…Participants who were female, younger, and more highly educated were more likely to use photoprotection than those who were male, older, and less educated 18 . A cross‐sectional study of 196 university students in Indonesia reported that 46% of participants had FST III and around 80–90% were aware of the most important risks of sun exposure (hyperpigmentation, skin cancer, photoaging, and photodermatoses) 19 . However, almost two‐thirds were not familiar with UV radiation wavelengths (UVA, UVB, and UVC) or that PA indicates protection against UVA 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin photoprotection indeed remains a vivid topic of research, witnessed by many recent and excellent papers. When limiting the literature search to these last 3 years, many works [38,[55][56][57][58][59][60][61][62][63][64][65][66] attest to the continuous efforts of all researchers dedicated, worldwide, to fundamental or applied advances in the skin photoprotection domain, best fitted to genetical/physiological or cultural specificities (skin phototypes, lifestyles, etc. ).…”
Section: Study Objective (N) Gender (W or M) Ages Protocol/methods Us...mentioning
confidence: 99%